2012
DOI: 10.1016/j.ijengsci.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

On modeling hydraulic fracture in proper variables: Stiffness, accuracy, sensitivity

Abstract: The problem of hydraulic fracture propagation is considered by using its recently suggested modified formulation in terms of the particle velocity, the opening in the proper degree, appropriate spatial coordinates and e-regularization. We show that the formulation may serve for significant increasing the efficiency of numerical tracing the fracture propagation. Its advantages are illustrated by re-visiting the Nordgren problem. It is shown that the modified formulation facilitates (i) possibility to have vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 22 publications
1
69
0
Order By: Relevance
“…Combining (41) and (33) with (46), after some algebra and integration, gives the following relation, which is valid for any real κ:…”
Section: Hf Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining (41) and (33) with (46), after some algebra and integration, gives the following relation, which is valid for any real κ:…”
Section: Hf Modelmentioning
confidence: 99%
“…Such an approach for the 1D PKN model has already been presented in [32,46,68] while its generalization, introducing explicit relations between crack tip asymptotics and crack propagation speed for all classical 1D models, can be found in [69]. It was shown that, when properly combined with other numerical devices, the algorithm represents an accurate and universal tool, which allows one to circumvent the main problems found in classical approaches used to establish the crack tip position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study is not concerned with the modelling of the fracture propagation (see, for instance [7][8][9][10][11]) or with the fluid flow (e.g. [12][13][14][15][16][17][18][19]).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This type of problem is most notably encountered in hydraulic fracturing technologies, with respect to the slurry flow inside the fracture (see, e.g., [6,7] and references therein).…”
Section: Introductionmentioning
confidence: 99%